Analysis and Monitoring Technology of Upper Seam Mining in Multiunderlayer Goaf. (22nd July 2021) - Liang, Han; Li, Pengfei; Cao, Chen
Abstract : Based on the background of close coal seam mining in the Qianjiaying coal mine, Tangshan, China, the feasibility of the upper seam mining in complex underlaying goaf is analysed using the roof caving analysis and numerical method. The deformation of the mining seam and roadways is monitored and analysed by field measurement and 3D laser scanning. The deformation characteristics of #5 seam after mining 1378P, 2071P, 2072P, and 2091P working panels with a depth of 39–54 m below the #5 seam are analysed using roof caving analysis and numerical method. Results show that the maximum deformation of #5 seam in the superimposed area of the lower goafs reaches 2.5 m and the maximum deformation in the single coal goaf is 1.5 m. The maximum seam inclination is 1.9°. The subsidence of the floor of 1359P roadways is obtained by field measurement, and the result is consistent with numerical calculation. ZEB-HORIZON 3D laser scanner was used to measure and model the roadway deformation. Based on the analysis of multiple scanning data, the deformation of the 1359P roadways was obtained. Results show that the deformation of the surrounding rock of the roadway is not great, the maximum displacement of the roof fall is 30 mm, and the maximum rib convergence is 25 mm. It can be concluded that the #5 seam can be recovered in this complex underlying lower seams' mining condition.